CORPORATE GOVERNANCE, INSTITUTIONAL OWNERSHIP, FREE CASH FLOW AND INVESTMENT EFFICIENCY: EVIDENCE OF INDONESIAN AGRICULTURE FIRM - Muchtar, Darmawati; Bensaadi, Iswadi; Husein, Ratna; Abdul Gani, Azhari (CV. Radja Publika, 2021)
The purpose of this study is to examine the determinants of investment efficiency with focuses on corporate governance, ownership structure, audit committee and free cash flow as the main factor. The 17 firms of Agriculture sector were selected as the sample from 2007 to 2019, hence this study have an unbalance panel data with total of 178 observations. The listed firm of Agriculture sector still slightly compared to others sectors in Indonesia Stock Exchange. Panel fixed effect model estimation was employed to test the relationship and hypotheses developed. The results show that board size has positive and significant effect on investment efficiency and contrary result to board of commissioners, it has negative insignificant. This indicates that large board size lead to increase the investment decision at optimal level. Moreover, the Audit committee and institutional ownership seem to have negative effect and significantly on investment efficiency. This means that when firms increase the number of audit committee and also the portion of share is owned by institution would lead to decrease investment efficiency. However, free cash flow have positive and significantly affect investment efficiency. This finding supports the expected hypothesis, which is increase the FCF lead to increase the investment efficiency and in this case, the managers act to maximize the firm value.